SEKOLAH MENENGGAH KEJURUAN NEGERI SE-KECAMATAN LUBUK BEGALUNG PADANG - METHA JENYUSYA PUTRI (Jurnal Bahana Manajemen Pendidikan, 2016)
The aim of this study is to see how the management of facilities and infrastructure in the country vocational schools in the district Lubuk Begalung Padang. The population was 59 taken by simple random sampling. The instrument of this research is the question Likert scale models that have been tested for validity and reliability. Data was analyzed using the values and average performance levels. These results show the management of facilities and infrastructure of learning by teachers in public vocational schools in the district in the Lubuk Begalung Padang enough category.